Ethnopharmacological study of plants sold for therapeutic purposes in public markets in Northeast Brazil. (22nd August 2015) - de Carvalho Nilo Bitu, Vanessa; de Carvalho Nilo Bitu, Valdeneide; Matias, Edinardo Fagner Ferreira; de Lima, Wenderson Pinheiro; da Costa Portelo, Aline; Coutinho, Henrique Douglas Melo; de Menezes, Irwin Rose Alencar
Abstract: Ethnopharmacological relevance: Studies of ethnobiological nature favor the rescue of popular culture, preventing important cultural and biological information from being lost over time. Another interesting point is that it can support bioprospecting studies focusing on the discovery of new drugs. Objective of the study: Our aim was to conduct a survey of plants sold for therapeutic purposes in public markets in the Crajubar Triangle in Northeast Brazil. Materials and methods: Using a questionnaire, data were collected regarding the part of the plant used, method of preparation, quantity needed, instructions for use and known adverse effects. From the data obtained, we calculated the relative importance of species and informant consensus factor. Results: Vendors indicated 91 useful species from a therapeutic point of view, distributed in 49 plant families. The preparation methods most frequently mentioned by informants were decoction, infusion, sauce with part of the plant in water and lozenge. The informants of this study mentioned bark, leaves, seeds and roots as parts of the plant most sold for therapeutic use. Disorders of the digestive system was the disease/disorder category with the highest consensus among the vendors, and the species Ximenia americana, Lippia gracillis, Stryphnodendron rotundifolium, Anacardium occidentale, Hymenaea courbail, Myracrodruon urundeuva, Amburana cearensis and Himatanthus drasticus were the most versatile among the plants sold in markets. Conclusions: Vendors indicated 91 species belonging to 49 botanical families and 89 genera. The most frequent forms of preparation were decoction, infusion and sauce made with part of the plant in water. The most common form of administration was oral. Bark and leaves were the plant parts most used. Thirteen species showed great versatility regarding their use. We noted 291 indications for use in 13 disease/disorder categories. Graphical abstract: Marketing and method of preparation of medicinal plants. (A) Public market in the Crajubar Triangle; (B) plant material set out on tables for sale; (C) parts of plants sold; (D) method of preparing plants for use.